Faktor yang Mempengaruhi Sertifikasi Halal Produk bagi Mahasiswa UIN Sunan Gunung Djati Bandung - Hestiani Fauziyyah; Widiawati Widiawati; Vemy Suci Asih (Journal of Applied Islamic Economics and Finance, 2021)
This study discusses the relationship between the level of understanding of students as (X1) and awareness as (X2) of halal product certification as (Y) with UIN Bandung students as research targets. The method used in this study is a survey method with questionnaires distributed by getting 100 respondents with a quantitative approach. The purpose of this study is to find out how much influence it has on each variable with the results showing that student understanding (X1) has a positive and significant effect on the Halal Certified Product variable (Y), and the influence of student awareness (X2) has a positive and significant impact on the Halal Certified Product variable. (Y). So the awareness and knowledge of students has a relationship with halal-certified products of 0.589. Calculated by correlation test and determination test. The level of understanding and awareness of students at this time is a consideration for halal product certification.